ANALISIS PENGENDALIAN PERSEDIAAN OBAT DENGAN METODE ABC, EOQ, DAN ROP PADA INSTALASI FARMASI RUMAH SAKIT AL-IRSYAD SURABAYA - Juli Prastyorini (Jurnal MEBIS (Manajemen dan Bisnis), 2021)
Community needs are currently getting higher for health services. One of them is the Pharmacy Installation unit. Where the pharmacy unit provides services for the patient's drug needs and is responsible for the availability of drugs in the hospital. This research uses a descriptive qualitative approach. The purpose of this study was to control drug supplies in sufficient quantities at the time needed and at the lowest possible cost. Based on the calculation analysis using the ABC method, it was found that there were 60 drugs belonging to category A (14.5%) with an investment of 70.2% of the total drug use and an investment value of Rp. 882,491,602, category B as many as 116 types of drugs (28.3%) with a total investment of 20.3% of the total drug use and an investment value of Rp. 254,186,353, and category C as many as 235 types of drugs (57.5%) with an investment of 9.5% of the total drug use and an investment value of Rp. 119,488,153. And also based on the inventory calculation analysis, it was found that for 60 types of drugs included in category A that the optimum order quantity, namely theEOQ method varies from 14.2 to 6637.7 for each type of drug. The number of safety supplies varied from 3.7-1924 for each type of drug. As well as the reorder point, namely the ROP method varies from 6-3339 for each type of drug